The Effect Of Adding Concentrated Basil Extracts On Improving Stability Oxidative In Mayonnaise Product (Damascus University Journal of agriculture sciences, 2026)
The research was carried out in the laboratories of the Department of Food Science, College of Agriculture, University of Damascus, and in the laboratories of Biotechnology, Ministry of Higher Education, with the aim of studying the effect of adding different proportions of Ocimum basilicum basil extract concentrate and preservatives (potassium sorbate, and sodium benzoate) in a synergistic manner in a total ratio of 1000 ppm in mayonnaise product quality. Some chemical indicators of fresh and dried basil leaves were estimated. The moisture content of the fresh and dried leaves was (87% and 8.75%), the ash was (2%, and 13%), and the pH was (7.40, and 7.10), respectively. The total phenolic content, flavonoids, and the antioxidant activity of the basil leaf extract concentrate were estimated at (2.68 mg/g, 1.82 mg/g, and 74%), respectively. All prepared mayonnaise samples were subjected to measuring antioxidant activity, thiobarbituric acid (TBA), and acidity values during 30 days of storage, as sample M5 (1000 ppm basil leaf extract) showed during 30 days the highest antioxidant activity (77%), and the lowest TBA number. The pH values were (0.40-2.10), respectively, and the control sample M0 showed the lowest antioxidant activity (58%), and the highest TBA number and pH value (1.20-3), respectively. No significant differences were observed between the manufactured mayonnaise samples in terms of most sensory characteristics (taste, smell, texture, and general acceptability) with the exception of color, as a significant difference was observed between the two control samples and the preservatives sample (M1-M0) and the sample (M5).
Keywords: Basil Extracts; Preservatives; Mayonnaise; Chemical Indicators; Sensory Properties